2013
DOI: 10.1080/15321819.2012.683502
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Anti-Hepatitis a Virus Immunoglobulin G Antibody Among Healthcare Facility Attendees in Osogbo, Nigeria

Abstract: The objectives of this study were to determine the prevalence of anti-hepatitis A virus (HAV) immunoglobulin G (IgG) antibody and associated factors among residents of Osogbo, a town in Nigeria with inadequate environmental sanitation and a shortage of potable water. This is a health facility-based study. Ninety one consenting, asymptomatic attendees of public healthcare facilities in Osogbo, Osun State, Nigeria, were consecutively selected for this study. Plasma samples of the study participants were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Eighteen studies (reported in 19 articles) of hepatitis A seroprevalence in West-African countries have been published [Table 1], including four from Cameroon,13141517 three each from Nigeria91020 and Senegal,21222326 two from Liberia,1924 and one each from Burkina Faso,8 Cabo Verde,18 Côte d’Ivoire,11 Gambia,25 Guinea,16 and Sierra Leone 12. Three studies published data collected in or after 2009,8910 one presented data from the early 2000s,11 six reported on data collected between 1985 and the mid-1990s,121314151617 and the remaining eight studies described data collected in the 1970s and early 1980s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies (reported in 19 articles) of hepatitis A seroprevalence in West-African countries have been published [Table 1], including four from Cameroon,13141517 three each from Nigeria91020 and Senegal,21222326 two from Liberia,1924 and one each from Burkina Faso,8 Cabo Verde,18 Côte d’Ivoire,11 Gambia,25 Guinea,16 and Sierra Leone 12. Three studies published data collected in or after 2009,8910 one presented data from the early 2000s,11 six reported on data collected between 1985 and the mid-1990s,121314151617 and the remaining eight studies described data collected in the 1970s and early 1980s.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies published data collected in or after 2009,8910 one presented data from the early 2000s,11 six reported on data collected between 1985 and the mid-1990s,121314151617 and the remaining eight studies described data collected in the 1970s and early 1980s. (Note that the results from older studies showing waning immunity among older adults16192526 may be attributable to the HAV IgG/IgM assay in use in the 1970s and early 1980s, which was found to have poor reliability for serum samples with low titres 27.…”
Section: Resultsmentioning
confidence: 99%
“…In Nigeria, although hepatitis of other viral origin is widely recognized, [19][20][21] the HEV situation is still largely unknown because incidence of the disease and its etiologic agent are likely underreported. Human HEV genotype 2 infection in Nigeria has been documented 14 and the prevalence of anti-HEV antibodies in humans is~13.4%.…”
Section: Discussionmentioning
confidence: 99%
“…'nın Nijerya'da sağlık kuruluşuna müracaat eden bireylerin % 98.9'u anti-HAV IgG antikoru bakımından seropozitifti. Nijerya'da hepatit A aşısı henüz ulusal programda yer almamaktadır ve hastalık ülkede endemik olarak görüldüğü için bu oran çok yüksek olarak bulunmuştur (31). Bizim çalışmamızdaki seropozitifliğin düşük oluş nedeni; katılımcıların çoğunluğunun sosyokültürel seviyelerinin ve altyapı sistemlerinin iyi olduğu bölgelerde ikamet etmelerinden kaynaklanmış olabileceğini düşünmekteyiz.…”
Section: Introductionunclassified